The Effectiveness of the Project Teaching Strategy in Developing Archaeological Excavation Skills among School Students in Jordan: Deir Al-Layyat Secondary School for Girls as a Model - Al-Daire, Jihad; Odat, Tameem (Dirasat: Educational Sciences, 2021)
The current study aims to reveal the effectiveness of the project teaching strategy in developing archaeological excavation skills among school students in Jordan: Deir Al-Layyat Secondary School for Girls as a model. This study adopted the experimental approach, as the study sample members were selected from Deir al-Layyat school in Jerash governorate, and their number reached (20) students from grades: eighth, ninth, and tenth. It was prepared as a project teaching strategy, and two tools: testing the concepts of archaeological excavation, and measuring the skills of archaeological excavation, and validity and reliability were achieved for them. Achieve validity and reliability coefficients for the test. The results revealed the effectiveness of the project teaching strategy in developing the archaeological excavation concepts and skills of female students from Deir Al Layyat Secondary School in Jerash. The researchers recommended the necessity of incorporating the study investigations into the concepts and skills of archaeological excavation, training teachers on the project teaching strategy, and conducting descriptive and experimental studies that enhance the teaching of archeology in the school education system.